2015 International Conference on Industrial Engineering and Operations Management (IEOM) 2015
DOI: 10.1109/ieom.2015.7093849
|View full text |Cite
|
Sign up to set email alerts
|

A queuing model for health care pharmacy using software Arena

Abstract: This paper focuses on improving and build a discrete event simulation model for modeling outpatient pharmacy workflow queuing system with the intent of exploring options for designing an efficient the queuing system of KKUH outpatient pharmacy Riyadh KSA. Simulation models of existing workflows in the pharmacy for KKUH outpatient pharmacy were created using discrete event simulation software (Arena). The data is collected for each server containing seven servers. Model inputs included prescription arrival time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…This could be due to the fact that the pharmacy wants to maintain a constant stock level in accordance with the afore-mentioned business policy, so there is a need for frequent small deliveries. The delivery processing time of defined delivery groups corresponded to the lognormal distributions with different parameters, which is comparable to the results obtained in the paper [23], but different from the findings of the authors in the paper [21] where the patient service time (patient processing time) had been modelled by the exponential distribution.…”
Section: Q2supporting
confidence: 56%
See 1 more Smart Citation
“…This could be due to the fact that the pharmacy wants to maintain a constant stock level in accordance with the afore-mentioned business policy, so there is a need for frequent small deliveries. The delivery processing time of defined delivery groups corresponded to the lognormal distributions with different parameters, which is comparable to the results obtained in the paper [23], but different from the findings of the authors in the paper [21] where the patient service time (patient processing time) had been modelled by the exponential distribution.…”
Section: Q2supporting
confidence: 56%
“…Different approaches to pharmacy process improvement have been found in literature, including implementation of automation [16], simulations and mathematical optimization [17][18][19][20][21][22][23][24][25][26], and improvement methodologies [27][28][29]. James et al [16] investigated the influence of automation on reducing errors in dispensation of medication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data were collected using stopwatch. Based on the analysis of the data which involved various scenarios, the result found from the simulation model shows that long waiting time exist in the system and simulation model basically helps to reduce the patients' waiting time and improve the service quality [8]. A suitable queueing theory and simulation technique has been developed in this study to optimize the management of studied outpatient pharmacy.…”
Section: Simulationmentioning
confidence: 99%
“…According to the previous literature, the study showed that the researchers utilised a simulation model to demonstrate the waiting time in the system (Ali & Kassam, 2017;Aziati & Hamdan, 2018;Luo et al, 2016). According to Alhaag et al (2015), the primary goal of the simulation model is to minimise patient waiting times while simultaneously improving service quality.…”
Section: Introductionmentioning
confidence: 99%